CONTINUITY OF CARE IN MRS. T WITH BREAST MILK DAM AT THE BUNDA CLINICNIETA DELI SERDANG REGENCY PROVINCE NORTH SUMATRA IN 2024 - Margaretha Lisna; Srilina Br Pinem; Merdila Telaumbanua; Dwi Hasanah; Julianti; Fitri Novita; Dyanti SR Butarbutar, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Basically, in health development in Indonesia, it aims to increase awareness, willingness and ability to live a healthy life for everyone so that Indonesia's health is achieved as high as possible. The Maternal Mortality Rate (MMR) in Indonesia is still very high from the global SDGs to reduce the MMR to 183,000 per 100,000 KH in 2014. Seeing this condition, strategic and comprehensive efforts are needed to achieve reducing the AKI to 183 per 100,000 KH by 2030 and a reduction in mortality of at least 5.5% per year is needed (Permenkes No. 21 of 2020). The maternal mortality rate (MMR) in 2021 is 7,389 people in Indonesia. The increase in maternal mortality rate (AKI) is high after compared to the previous 2020. Where the maternal mortality rate (AKI) is 4,627 people in Indonesia. (Indonesian Health Profile 2021). From the province of North Sumatra during 2020, the number of deaths reached 187 cases from 299.98 birth targets from the number of infant deaths of 751 cases from 198 live birth targets (Indonesian Health Profile 2020).